Peran Strategis Dewan Pengawas Syariah dalam Mewujudkan Keuangan Syariah Berbasis Etika - Alfian Widiyanto; Dini Selasi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
The Sharia Supervisory Board (SSB) holds a pivotal role in ensuring Islamic financial institutions operate in full compliance with Sharia principles. Its responsibilities include issuing fatwas, overseeing daily operations, and ensuring the integrity of financial products and services offered by these institutions. The SSB’s role is critical in maintaining public trust and aligning financial practices with Islamic values. However, significant challenges arise, such as the increasing complexity of financial instruments, rapid technological advancements, and varying interpretations of Sharia principles across jurisdictions. Moreover, public awareness of Islamic finance remains low, and the risk of conflicts of interest in SSB oversight persists. To overcome these challenges, the SSB must strengthen its expertise through continuous education, collaborate with scholars and regulators, and actively engage in public literacy initiatives. Harmonization of Sharia standards at a global level is also essential to navigate the interconnected nature of modern finance. The SSB’s success in addressing these challenges ensures the sustainability of Islamic financial systems while fostering ethical and equitable economic growth.